Mineral Requirements for Military Personnel: Levels Needed for Cognitive and Physical Performance During Garrison Training - Institute of Medicine (The National Academies Press, 2006)
The U.S. Army Health Risk Appraisal group surveyed 400,000 active duty U.S. Army personnel in the late 1990s to determine whether or not those personnel met the dietary objectives of Healthy People 2000 (HP2000), a national agenda for health promotion and disease prevention. As reported by Yore et al. (2000), Army personnel generally did not meet the HP2000 goals for nutrition even though significant progress had been made during 1991-1998. Although the specific aspects of diet that would be relevant to this Committee on Mineral Requirements for Cognitive and Physical Performance of Military Personnel are lacking, the findings from this survey suggest that there are dietary problems in the military population. The potential for adverse effects of marginal mineral deficiencies among soldiers engaged in training or military operations and the prospect of improving military performance through mineral intakes have spurred the military's interest in this area of nutrition. Mineral Requirements for Military Personnel provides background information on the current knowledge regarding soldiers' eating behaviors as well as on the physical and mental stress caused by military garrison training or operations. This report also offers facts on the mineral content of rations and its intake by military personnel and addresses the potential effects of nutrient deficiencies due to inadequate intake or higher requirements during military operations. Mineral Requirements for Military Personnel provides information and recommendations on the development and uses of MDRIs and a description of strategies to increase intake of specific minerals, whether via usual foods, fortification, or supplementation. This report features a description of the metabolism and needs for selected minerals by military personnel under garrison training, recommendations on mineral intake levels, and an assessment of mineral level adequacy in operational rations. This report also includes a prioritization of the research needed to answer information gaps and details of study designs required to gain such information.
Keywords: Conflict and Security Issues; Food and Nutrition

Dietary Reference Intakes for Vitamin C, Vitamin E, Selenium, and Carotenoids - Institute of Medicine (The National Academies Press, 2000)
This volume is the newest release in the authoritative series of quantitative estimates of nutrient intakes to be used for planning and assessing diets for healthy people. Dietary Reference Intakes (DRIs) is the newest framework for an expanded approach developed by U.S. and Canadian scientists. This book discusses in detail the role of vitamin C, vitamin E, selenium, and the carotenoids in human physiology and health. For each nutrient the committee presents what is known about how it functions in the human body, which factors may affect how it works, and how the nutrient may be related to chronic disease. Dietary Reference Intakes provides reference intakes, such as Recommended Dietary Allowances (RDAs), for use in planning nutritionally adequate diets for different groups based on age and gender, along with a new reference intake, the Tolerable Upper Intake Level (UL), designed to assist an individual in knowing how much is "too much" of a nutrient.
Keywords: Food and Nutrition

Eat for Life: The Food and Nutrition Board's Guide to Reducing Your Risk of Chronic Disease - Institute of Medicine; National Academy of Sciences (The National Academies Press, 1992)
Results from the National Research Council's (NRC) landmark study Diet and health are readily accessible to nonscientists in this friendly, easy-to-read guide. Readers will find the heart of the book in the first chapter: the Food and Nutrition Board's nine-point dietary plan to reduce the risk of diet-related chronic illness. The nine points are presented as sensible guidelines that are easy to follow on a daily basis, without complicated measuring or calculating—and without sacrificing favorite foods. Eat for Life gives practical recommendations on foods to eat and in a "how-to" section provides tips on shopping (how to read food labels), cooking (how to turn a high-fat dish into a low-fat one), and eating out (how to read a menu with nutrition in mind). The volume explains what protein, fiber, cholesterol, and fats are and what foods contain them, and tells readers how to reduce their risk of chronic disease by modifying the types of food they eat. Each chronic disease is clearly defined, with information provided on its prevalence in the United States. Written for everyone concerned about how they can influence their health by what they eat, Eat for Life offers potentially lifesaving information in an understandable and persuasive way. Alternative Selection, Quality Paperback Book Club
Keywords: Food and Nutrition

Nutrition During Pregnancy: Part I: Weight Gain, Part II: Nutrient Supplements - Institute of Medicine (The National Academies Press, 1990)
In Part I of Nutrition During Pregnancy, the authors call for revisions in recommended weight gains for pregnant women. They explore relationships between weight gain during pregnancy and a variety of factors (e.g., the mother's weight for height before pregnancy) and places this in the context of the health of the infant and the mother. They present specific target ranges for weight gain during pregnancy and guidelines for proper measurement. Part II addresses vitamin and mineral supplementation during pregnancy, examining the adequacy of diet in meeting nutrient needs during pregnancy and recommending specific amounts of supplements for special circumstances. It also covers the effects of caffeine, alcohol, cigarette, marijuana, and cocaine use and presents specific research recommendations.
Keywords: Food and Nutrition

Nutritional Needs in Hot Environments: Applications for Military Personnel in Field Operations - Institute of Medicine (The National Academies Press, 1993)
This volume examines the current state of knowledge concerning the influence of a hot environment on nutrient requirements of military personnel. A parallel concern is ensuring that performance does not decline as a result of inadequate nutrition. The committee provides a thorough review of the literature in this area and interprets the diverse data in terms of military applications. In addition to a focus on specific nutrient needs in hot climates, the committee considers factors that might change food intake patterns and therefore overall calories. Although concern for adequate nutrition for U.S. soldiers in Saudi Arabia prompted the initiation of this project, its scope includes the nutrient needs of individuals who may be actively working in both hot-dry and hot-moist climates.
Keywords: Food and Nutrition

Food Components to Enhance Performance: An Evaluation of Potential Performance-Enhancing Food Components for Operational Rations - Institute of Medicine (The National Academies Press, 1994)
The physiological or psychological stresses that employees bring to their workplace affect not only their own performance but that of their co-workers and others. These stresses are often compounded by those of the job itself. Medical personnel, firefighters, police, and military personnel in combat settings—among others—experience highly unpredictable timing and types of stressors. This book reviews and comments on the performance-enhancing potential of specific food components. It reflects the views of military and non-military scientists from such fields as neuroscience, nutrition, physiology, various medical specialties, and performance psychology on the most up-to-date research available on physical and mental performance enhancement in stressful conditions. Although placed within the context of military tasks, the volume will have wide-reaching implications for individuals in any job setting.
Keywords: Food and Nutrition

Caffeine for the Sustainment of Mental Task Performance: Formulations for Military Operations - Institute of Medicine (The National Academies Press, 2001)
This report from the Committee on Military Nutrition Research reviews the history of caffeine usage, the metabolism of caffeine, and its physiological effects. The effects of caffeine on physical performance, cognitive function and alertness, and alleviation of sleep deprivation impairments are discussed in light of recent scientific literature. The impact of caffeine consumption on various aspects of health, including cardiovascular disease, reproduction, bone mineral density, and fluid homeostasis are reviewed. The behavioral effects of caffeine are also discussed, including the effect of caffeine on reaction to stress, withdrawal effects, and detrimental effects of high intakes. The amounts of caffeine found to enhance vigilance and reaction time consistently are reviewed and recommendations are made with respect to amounts of caffeine appropriate for maintaining alertness of military personnel during field operations. Recommendations are also provided on the need for appropriate labeling of caffeine-containing supplements, and education of military personnel on the use of these supplements. A brief review of some alternatives to caffeine is also provided.
Keywords: Food and Nutrition; Transportation and Infrastructure

Nutrient Requirements of Dairy Cattle: Seventh Revised Edition, 2001 - National Research Council (The National Academies Press, 2001)
This widely used reference has been updated and revamped to reflect the changing face of the dairy industry. New features allow users to pinpoint nutrient requirements more accurately for individual animals. The committee also provides guidance on how nutrient analysis of feed ingredients, insights into nutrient utilization by the animal, and formulation of diets to reduce environmental impacts can be applied to productive management decisions. The book includes a user-friendly computer program on a compact disk, accompanied by extensive context-sensitive "Help" options, to simulate the dynamic state of animals. The committee addresses important issues unique to dairy science-the dry or transition cow, udder edema, milk fever, low-fat milk, calf dehydration, and more. The also volume covers dry matter intake, including how to predict feed intake. It addresses the management of lactating dairy cows, utilization of fat in calf and lactation diets, and calf and heifer replacement nutrition. In addition, the many useful tables include updated nutrient composition for commonly used feedstuffs.
Keywords: Agriculture; Food and Nutrition

Nutrition During Pregnancy and Lactation: An Implementation Guide - Institute of Medicine (The National Academies Press, 1992)
Authorities agree that nutritional care for pregnant, about-to-be pregnant, and nursing women can prevent health problems that are costly in terms of both dollars and quality of life. Yet many women still receive little guidance regarding maternal nutrition. Now, health care professionals can turn to a handy, practical guide for help in smoothly integrating maternal nutritional care into their practices. Nutrition During Pregnancy and Lactation provides physicians, nurses, primary care providers, and midwives with a ready-made, step-by-step program for helping new mothers. The guide—based on the two most authoritative volumes available on the topic, both from the Institute of Medicine—Nutrition During Pregnancy (1990) and Nutrition During Lactation (1991)—makes the findings and recommendations detailed in these books readily accessible for daily use. In keeping with recommendations by the U.S. Surgeon General, the guide promotes breastfeeding and includes practical information for mothers on how to breastfeed. Providing background details, resource lists, and a "toolbox" of materials, this implementation guide makes nutritional care simple and straightforward. Part I walks the health care professional through the process of providing nutritional advice for new mothers—from the pre-pregnancy questionnaire to the final postpartum visit. It includes helpful tools such as weight charts and checklists to follow during each patient visit. It also offers suggestions on encouraging nutritional eating habits and helping patients with problems such as nausea and nursing twins. Part II offers a wide range of practical information and guidelines on important topics, such as serving culturally diverse populations, making dietary assessments throughout pregnancy and lactation, and providing dietary advice in understandable, day-to-day terms. The guide explains how to determine if patients need vitamin-mineral supplements and what regimens to recommend. And, it includes information on referring patients to federal food and nutrition programs. The guide is tabbed for quick reference and each page is designed for the reader to find information easily.
Keywords: Food and Nutrition; Health and Medicine

Science and Food: Today and Tomorrow - National Research Council (The National Academies Press, 1961)
Keywords: Food and Nutrition

Tumors of the Soft Tissues, by Arthur Purdy Stout and Raffaele Lattes - National Research Council (The National Academies Press, 1967)
Keywords: Food and Nutrition

Quality and Stability of Canned Meats: A Symposium Sponsored by the Quartermaster Food and Container Institute for the Armed Forces, Quartermaster Research and Development Command, U.S. Army Quartermaster Corps, Palmer House, Chicago, March 31 - April 1, 1953 - National Research Council (The National Academies Press, 1954)
Keywords: Food and Nutrition

Nutritional Needs in Cold and High-Altitude Environments: Applications for Military Personnel in Field Operations - Institute of Medicine (The National Academies Press, 1996)
This book reviews the research pertaining to nutrient requirements for working in cold or in high-altitude environments and states recommendations regarding the application of this information to military operational rations. It addresses whether, aside from increased energy demands, cold or high-altitude environments elicit an increased demand or requirement for specific nutrients, and whether performance in cold or high-altitude environments can be enhanced by the provision of increased amounts of specific nutrients.
Keywords: Food and Nutrition; Health and Medicine

Dietary Reference Intakes for Calcium, Phosphorus, Magnesium, Vitamin D, and Fluoride - Institute of Medicine (The National Academies Press, 1997)
Since 1941, Recommended Dietary Allowances (RDAs) has been recognized as the most authoritative source of information on nutrient levels for healthy people. Since publication of the 10th edition in 1989, there has been rising awareness of the impact of nutrition on chronic disease. In light of new research findings and a growing public focus on nutrition and health, the expert panel responsible for formulation RDAs reviewed and expanded its approach—the result: Dietary Reference Intakes. This new series of references greatly extends the scope and application of previous nutrient guidelines. For each nutrient the book presents what is known about how the nutrient functions in the human body, what the best method is to determine its requirements, which factors (caffeine or exercise, for example) may affect how it works, and how the nutrient may be related to chronic disease. The first volume of Dietary Reference Intakes includes calcium, phosphorus, magnesium, vitamin D, and fluoride. The second book in the series presents information about thiamin, riboflavin, niacin, vitamin B6, folate, vitamin B12, pantothenic acid, biotin, and choline. Based on analysis of nutrient metabolism in humans and data on intakes in the U.S. population, the committee recommends intakes for each age group—from the first days of life through childhood, sexual maturity, midlife, and the later years. Recommendations for pregnancy and lactation also are made, and the book identifies when intake of a nutrient may be too much. Representing a new paradigm for the nutrition community, Dietary Reference Intakes encompasses: Estimated Average Requirements (EARs). These are used to set Recommended Dietary Allowances. Recommended Dietary Allowances (RDAs). Intakes that meet the RDA are likely to meet the nutrient requirement of nearly all individuals in a life-stage and gender group. Adequate Intakes (AIs). These are used instead of RDAs when an EAR cannot be calculated. Both the RDA and the AI may be used as goals for individual intake. Tolerable Upper Intake Levels (ULs). Intakes below the UL are unlikely to pose risks of adverse health effects in healthy people. This new framework encompasses both essential nutrients and other food components thought to pay a role in health, such as dietary fiber. It incorporates functional endpoints and examines the relationship between dose and response in determining adequacy and the hazards of excess intake for each nutrient.
Keywords: Food and Nutrition

Vitamin C Fortification of Food Aid Commodities: Final Report - Institute of Medicine (The National Academies Press, 1997)
Keywords: Food and Nutrition

Nutritional Risk Assessment: Perspectives, Methods, and Data Challenges: Workshop Summary - Institute of Medicine (The National Academies Press, 2007)
For more than two decades, the practice of risk assessment has been applied to human public health issues, and policy makers have used the results of risk assessments in their decision-making process. Approaches for risk assessment have been developed for nonnutrients such as drugs, food additives, and pesticides, but approaches for risk assessment have received less attention in the nutrition area. Some aspects of the risk assessment approach used for nonnutrients are applicable to the assessment of risks related to nutrition. The overall approach, however, must be adapted and modified to take into account the unique aspects of nutrients, including the fact that both high and low nutrient intakes are associated with risk. Experience with the application of a risk assessment process to the setting of upper levels of intake for essential nutrients, for example, has uncovered a number of challenges. Adapting and developing risk assessment strategies for application in nutrition science could lead to improved approaches to the development of dietary and nutritional recommendations and thus is a topic of considerable interest. One nonscientific but overall challenge to nutritional risk assessment relates to increasing and improving communication among experts from key disciplines in ways that could inform the nutritional risk assessment process. Among these key disciplines are nutrition, toxicology, dietary exposure assessment, economics, risk analysis, and epidemiology. How can the perspectives and methods of these diverse fields be brought together to develop more effective approaches for quantitative nutritional risk assessment? How can they be applied to a spectrum of topics related to food and nutrition—micronutrients, macronutrients, dietary supplements, whole foods, food groups, and dietary patterns? How can they help overcome the data challenges that confront nutritional risk assessors? As a step toward improving the communication and sharing methods and information across disciplines, members of the Interagency Risk Assessment Consortium, the U.S. Health and Human Services Office of the Assistant Secretary for Planning and Evaluation, the Institute of Medicine's Food Forum, and the International Life Sciences Institute planned the Nutritional Risk Assessment Workshop. The workshop was held on February 28 and March 1, 2007, in Washington, D.C. This workshop, which was envisioned as one in a series, focused on opening a dialogue to explore the unique questions and challenges faced by nutritionists and the potential use of risk assessment methodologies to answer them. Nutritional Risk Assessment : Perspectives, Methods, and Data Challenges, Workshop Summary summarizes the happenings of this workshop.
Keywords: Food and Nutrition

Dietary Reference Intakes for Sodium and Potassium - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
As essential nutrients, sodium and potassium contribute to the fundamentals of physiology and pathology of human health and disease. In clinical settings, these are two important blood electrolytes, are frequently measured and influence care decisions. Yet, blood electrolyte concentrations are usually not influenced by dietary intake, as kidney and hormone systems carefully regulate blood values. Over the years, increasing evidence suggests that sodium and potassium intake patterns of children and adults influence long-term population health mostly through complex relationships among dietary intake, blood pressure and cardiovascular health. The public health importance of understanding these relationships, based upon the best available evidence and establishing recommendations to support the development of population clinical practice guidelines and medical care of patients is clear. This report reviews evidence on the relationship between sodium and potassium intakes and indicators of adequacy, toxicity, and chronic disease. It updates the Dietary Reference Intakes (DRIs) using an expanded DRI model that includes consideration of chronic disease endpoints, and outlines research gaps to address the uncertainties identified in the process of deriving the reference values and evaluating public health implications.
Keywords: Food and Nutrition

Dietary Reference Intakes for Water, Potassium, Sodium, Chloride, and Sulfate - Institute of Medicine (The National Academies Press, 2005)
Dietary Reference Intakes for Water, Potassium, Sodium, Chloride, and Sulfate The Dietary Reference Intakes (DRIs) are quantitative estimates of nutrient intakes to be used for planning and assessing diets for healthy people. This new report, the sixth in a series of reports presenting dietary reference values for the intakes of nutrients by Americans and Canadians, establishes nutrient recommendations on water, potassium, and salt for health maintenance and the reduction of chronic disease risk. Dietary Reference Intakes for Water, Potassium, Sodium, Chloride, and Sulfate discusses in detail the role of water, potassium, salt, chloride, and sulfate in human physiology and health. The major findings in this book include the establishment of Adequate Intakes for total water (drinking water, beverages, and food), potassium, sodium, and chloride and the establishment of Tolerable Upper Intake levels for sodium and chloride. The book makes research recommendations for information needed to advance the understanding of human requirements for water and electrolytes, as well as adverse effects associated with the intake of excessive amounts of water, sodium, chloride, potassium, and sulfate. This book will be an invaluable reference for nutritionists, nutrition researchers, and food manufacturers.
Keywords: Food and Nutrition

High-Energy, Nutrient-Dense Emergency Relief Food Product - Institute of Medicine (The National Academies Press, 2002)
The present study was conducted by an ad hoc subcommittee of the Committee on Military Nutrition Research. The Subcommittee on Technical Specifications for a High-Energy Emergency Relief Ration was established by the Food and Nutrition Board of the Institute of Medicine in response to a request from USAID and DOD to develop technical specifications for a product for use in food relief after natural disasters or other emergency situations around the world. The specifications are to be used by both agencies in their calls for bids from U.S. food manufacturers to supply such a product.
Keywords: Food and Nutrition

Dietary Reference Intakes: Applications in Dietary Assessment - Institute of Medicine (The National Academies Press, 2000)
Since 1994 the Institute of Medicine's Food and Nutrition Board has been involved in developing an expanded approach to developing dietary reference standards. This approach, the Dietary Reference Intakes (DRIs), provides a set of four nutrient-based reference values designed to replace the Recommended Dietary Allowances (RDAs) in the United States and the Recommended Nutrient Intakes (RNIs) in Canada. These reference values include Estimated Average Requirement (EAR), Recommended Dietary Allowance (RDA), Adequate Intake (AI), and Tolerable Upper Intake Level (UL). To date, several volumes in this series have been published. This new book, Applications in Dietary Assessment, provides guidance to nutrition and health research professionals on the application of the new DRIs. It represents both a "how to" manual and a "why" manual. Specific examples of both appropriate and inappropriate uses of the DRIs in assessing nutrient adequacy of groups and of individuals are provided, along with detailed statistical approaches for the methods described. In addition, a clear distinction is made between assessing individuals and assessing groups as the approaches used are quite different. Applications in Dietary Assessment will be an essential companion to any-or all-of the DRI volumes.
Keywords: Food and Nutrition